The Influence of Customer Perceived Quality, Customer Perceived Value and Product Availability on Customer Loyalty at Bread Roll Wisnu Jember UKM - Junaidi; M. Syarif Hidayatullah Elmas; Zalfa’ Nur Auliya Putri. P; Bahrul Ulum (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to know whether or not there is a variable influence customer perceived quality, customer perceived value and The availability of products for customer loyalty. Incidentally based sampling techniques, sampling up to 100 respondents. Respondents had to use the method of analysis of the data, reabilitas, the classic asumtion, multiple linear test, determination (R2) And the final hypothetical test. From this research the author found that the influence point is partial of the x1 variable: There is a significant influence of customer perceived quality on customer loyalty, which the value ttest (4,775) > t table (1,660) with significantly 0,000 < 0,05.